Determinants of Korean Trade Flows and their Geographical Destination - Milesi-Ferretti, Gian.; Giorgianni, Lorenzo (Washington, D.C. : International Monetary Fund, 1997)
This paper investigates the behavior of Korean trade flows during the last three decades and presents estimates of aggregate export and import equations. In particular, it considers different choices for scale and price variables and assesses the relative merits of these alternative specifications in terms of stability and forecasting performance. It also provides an assessment of the drastic change in the geographical destination of Korean exports during the 1990s.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet